A new strategy to obtain tetranuclear cobalt(ii) metal–organic frameworks based on the [Co4(μ3-OH)2] cluster: synthesis, structures and properties. Issue 38 (30th August 2016) - Li, Ke; Lv, Xiu-Xiu; Shi, Lu-Lu; Liu, Lu; Li, Bao-Long; Wu, Bing
Abstract : Three MOFs based on [Co4 (μ3 -OH)2 ] with 4-, 6- and 8-connected frameworks exhibit antiferromagnetic interactions and are good photocatalysts. Abstract : Three metal–organic frameworks (MOFs) {[Co4 (OH)2 (adc)6 (H2 O)5 ][Co2 (OH)(btrb)]2 ·8H2 O} n (1 ), {[Co4 (OH)2 (btrb)(nip)3 (H2 O)3 ]·4H2 O} n (2 ·4H2 O) and {[Co4 (OH)2 (btrb)(btc)2 (H2 O)2 ]·9H2 O} n (3 ·9H2 O) (btrb = 1, 4-bis(1, 2, 4-triazol-4-ylmethyl)benzene, H2 adc = 1, 3-adamantanedicarboxylic acid, H2 nip = 5-nitroisophthalic acid and H3 btc = 1, 3, 5-benzenetricarboxylic acid) were synthesized by a hydrothermal method.1 shows an unusual (3, 4)-connected 2D network with a point symbol of (4·6 2 )2 (4 2 ·6 2 ·8 2 ) based on [Co4 (μ3 -OH)2 ] and [Co2 (μ3 -OH)] units.2 is a 6-connected pcu topology based on the [Co4 (μ3 -OH)2 ] unit.3 is a rare (3, 8)-connected 3D framework with a rare point symbol of (4·5·6)2 (4 2 ·5 6 ·6 16 ·7 2 ·8 2 ) based on the [Co4 (μ3 -OH)2 ] unit. The magnetic measurements reveal that1–3 exhibit antiferromagnetic interactions between the adjacent cobalt(ii ) centers.1–3 are good photocatalysts for the degradation of methylene blue (MB). The 1, 2-position nitrogen atoms of the 4-substituted 1, 2, 4-triazole ligand act as strong σ-donators to form a quite stable coordination quadrangle with two metal ions. The btrb ligand containing two 4-substituted 1, 2, 4-triazole rings is favorable to form tetranuclear metal units. By the regulation of the multicarboxylate ligands, the connection number of [Co4 (μ3 -OH)2 ] clusters increases from 4 in1 to 6 in2 and then 8 in3 . This work presents a novel but effective method to design and regulate the connection number (4, 6 and 8 connected in this work) of MOFs with 4-substituted 1, 2, 4-triazole and rigid multicarboxylate ligands.